Stringent Primer Termination by an Archaeo-Eukaryotic DNA Primase - Bergsch, Jan; Devillier, Jean-Christophe; Jeschke, Gunnar; Lipps, Georg (Frontiers in Microbiology, 2021)
Priming of single stranded templates is essential for DNA replication. In recent years, significant progress was made in understanding how DNA primase fulfils this fundamental function, particularly with regard to the initiation. Equally intriguing is the unique property of archeao-eukaryotic primases to terminate primer formation at a well-defined unit length. The apparent ability to “count” the number of bases incorporated prior to primer release is not well understood, different mechanisms having been proposed for different species. We report a mechanistic investigation of primer termination by the pRN1 primase from Sulfolobus islandicus. Using an HPLC-based assay we determined structural features of the primer 5’-end that are required for consistent termination. Mutations within the unstructured linker connecting the catalytic domain to the template binding domain allowed us to assess the effect of altered linker length and flexibility on primer termination.